E-commerce - Laudon, Kenneth C.
For the undergraduate and graduate e-commerce course in any business discipline. The market-leading text for E-commerce. This comprehensive, market-leading text emphasizes the three major driving forces behind E-commerce--technology change, business development, and social issues--to provide a coherent conceptual framework for understanding the field. The sixth edition--including all of the data, figures, and tables in the book--has been updated through August 2009 with the latest marketing and business intelligence available from eMarketer, Pew Internet & American Life Project, Forrester Research, Jupiter Research, Gartner, and other industry sources